1992
DOI: 10.1084/jem.176.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine RANTES released by thrombin-stimulated platelets is a potent attractant for human eosinophils.

Abstract: SummaryThrombin stimulation of human platelets results in the release of a preformed proteinaceous human eosinophil (Eo)-chemotactic activity. By the use of different high-performance liquid chromatography techniques, two Eo-chemotactic polypeptides (EoCPs), tentatively termed EoCP-1 and EoCP-2, were purified to homogeneity. Upon SDS-PAGE analysis, these chemotaxins showed molecular masses near 8 kD. NH2-terminal amino acid sequence analysis revealed identical sequences for both EoCP-1 and EoCP-2, which are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
393
1
5

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(412 citation statements)
references
References 30 publications
13
393
1
5
Order By: Relevance
“…5 Increased production of RANTES would be expected to increase the level of inflammatory cell recruitment, as it is one of the major chemoattractant proteins for eosinophils 4 and others (basophils, mast cells and T lymphocytes) into asthmatic airways after allergen challenge. 21,22 The role of this particular pathway to immune regulation is also supported by observations that the GATA transcription motif in position 403 of the chemokine RANTES gene is associated with a number of inflammatory-mediated disease including rheumatoid arthritis 10 in delaying the progression of HIV infection, 23 and in the expression of childhood atopic dermatitis. 24 We have strengthened the evidence that this association is real by demonstrating familial transmission with asthma and atopy and by confirming that the association is predominantly toward atopy and atopic asthma.…”
Section: Discussionmentioning
confidence: 89%
“…5 Increased production of RANTES would be expected to increase the level of inflammatory cell recruitment, as it is one of the major chemoattractant proteins for eosinophils 4 and others (basophils, mast cells and T lymphocytes) into asthmatic airways after allergen challenge. 21,22 The role of this particular pathway to immune regulation is also supported by observations that the GATA transcription motif in position 403 of the chemokine RANTES gene is associated with a number of inflammatory-mediated disease including rheumatoid arthritis 10 in delaying the progression of HIV infection, 23 and in the expression of childhood atopic dermatitis. 24 We have strengthened the evidence that this association is real by demonstrating familial transmission with asthma and atopy and by confirming that the association is predominantly toward atopy and atopic asthma.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, linkage and molecular epidemiology studies have shown that several other such mediators (IL-4, IL-5, IL-13, interferon-␥) are candidates for susceptibility to asthma. [3][4][5] RANTES is produced by T-lymphocytes and monocytes and acts as a chemoattractant for several cell types (eg, mast cells, basophils, T-lymphocytes, eosinophils) 6,7 which are central to the inflammatory cascade. Therefore, increased production of RANTES would be predicted to result in enhanced recruitment of proinflammatory cells to the target site, precipitating an amplified local inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…This mediator has the ability to attract several types of inflammatory cells including monocytes, eosinophils and memory Thelper (Th) cells to the site of inflammation. 6,7 Furthermore, increased levels of RANTES and other members of the C-C family of chemokines (MIP-1␣, MCP-1) have been detected in the nasal secretions of atopic patients exposed to local allergen challenge 8 and were found in higher levels in the bronchial lavage fluid of patients with active asthma. 9 RANTES has also been found at significantly higher levels in patients during asthma attacks than in those with asymptomatic stages or in controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is a potent chemoattractant for eosinophils, lymphocytes, monocytes, and basophils [3][4][5]. RANTES is expressed in activated T lymphocytes, airway epithelial cells, platelets, fibroblasts, and renal epithelial and mesangial cells [6].…”
Section: Introductionmentioning
confidence: 99%